Kudeta di Myanmar: Kronologi Peristiwa, Dampak Sosial-Politik, Reaksi Internasional, dan Pendekatan Hukum Internasional - Triadi, Irwan; Lubis, William Haposan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Myanmar is one of the countries that is part of Southeast Asia, whose government has been led by the Military since 1962. The Military, which has long held high power in Myanmar, certainly will not let go of its power just like that, they do everything they can to continue to hold the highest power. If the highest power has been seized from the Myanmar Military, they can do everything they can to prevent it from happening, including by overthrowing the power that has been taken over. This study uses normative and qualitative legal research methods. This study uses a normative legal research method (normative juridical), namely research that focuses on the study of applicable legal norms, both those written in laws and regulations and those that live and develop in legal practice. The method used is qualitative, supported by reference sources from journals related to international law and also news sources about the Myanmar Coup case. The military coup that took place in Myanmar on February 1, 2021 was not just a regime change, but a turning point that destroyed the foundations of democracy and triggered widespread suffering for its people. By arresting Aung San Suu Kyi, Win Myint, and other elected figures, the junta buried the legitimate election process and upheld power as a tool of power. As a result, hundreds to thousands of citizens died in protests, tens of thousands were detained without trial, and millions fell into poverty when the national economy collapsed and food supplies were disrupted. The results of the study show that international legal intervention can be carried out on humanitarian grounds.